Non‐invasive renal artery embolization for renal dysplasia accompanied by hypertension. Issue 1 (February 2014) - Yanagida, Hidehiko; Tabata, Nobutada; Sugimoto, Keisuke; Izu, Akane; Wada, Norihisa; Sakata, Naoki; Okada, Mitsuru; Takemura, Tsukasa
Abstract Renovascular hypertension caused by renal dysplasia often is resistant to drug therapy. For a 14‐year‐old girl with such refractory hypertension, a non‐invasive right renal ablation by embolization with anhydrous ethanol using a shepherd 's‐crook' balloon catheter, was done. Blood pressure then rapidly normalized. Apart from mild fever after the procedure, no adverse effects occurred. In patients with mild renal artery stenosis and hypertension resistant to anti‐hypertensive drug therapy, renal artery embolization may be a useful option.